2022
DOI: 10.1007/s00259-022-06036-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting clinically significant prostate cancer with a deep learning approach: a multicentre retrospective study

Abstract: Purpose This study aimed to develop deep learning (DL) models based on multicentre biparametric magnetic resonance imaging (bpMRI) for the diagnosis of clinically significant prostate cancer (csPCa) and compare the performance of these models with that of the Prostate Imaging and Reporting and Data System (PI-RADS) assessment by expert radiologists based on multiparametric MRI (mpMRI). Methods We included 1861 consecutive male patients who underwent radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…For the diagnosis based on medical images, compared to the radiologists' interpretation, the main advantage of deep learning models is that they can not only mine the subtle and even invisible image features, 17,33 but also analyze the features concurrently using a multivariable method, therefore achieving higher sensitivity and specificity. 17 The higher performance of TransCL relative to radiologists' interpretation in the current study was consistent with previous studies on the diagnosis of PCa 16,23,34 and other tumors. [35][36][37][38] Thus, the proposed deep learning models, particularly TransCL which combined TransNet signature and the clinical characteristics, have potential to aid radiologists in the pre-operation diagnosis of AP presence.…”
Section: Thesupporting
confidence: 91%
See 2 more Smart Citations
“…For the diagnosis based on medical images, compared to the radiologists' interpretation, the main advantage of deep learning models is that they can not only mine the subtle and even invisible image features, 17,33 but also analyze the features concurrently using a multivariable method, therefore achieving higher sensitivity and specificity. 17 The higher performance of TransCL relative to radiologists' interpretation in the current study was consistent with previous studies on the diagnosis of PCa 16,23,34 and other tumors. [35][36][37][38] Thus, the proposed deep learning models, particularly TransCL which combined TransNet signature and the clinical characteristics, have potential to aid radiologists in the pre-operation diagnosis of AP presence.…”
Section: Thesupporting
confidence: 91%
“…Furthermore, some subtle, and even invisible features (eg, textural features, advanced features), that are also associated with PCa aggressiveness and progression may be missed. [14][15][16] Deep learning is an artificial intelligence (AI) methodology that can convert medical images into high-dimensional, mineable, and quantitative features that are difficult to detect through visual assessment. 14,17 Using the high-throughput and deeply mined features as input information, a deep learning model can output a quantitative score indicating the risk of adverse outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, for the diagnosis in TZ of this study, MRI‐TBx detected 23% cases missed by TRUS‐SBx in which 68% were csPCa, and in 22% cases Gleason score was upgraded by MRI‐TBx. Previous research has demonstrated that MRI‐TBx could detect PCa with a higher Gleason score compared to TRUS‐SBx due to the most suspicious lesions precisely identified by MRI 23–25 . It was shown that prebiopsy MRI scan could guide a more effective biopsy for csPCa and thus was recommended by many guidelines 10,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that MRI-TBx could detect PCa with a higher Gleason score compared to TRUS-SBx due to the most suspicious lesions precisely identified by MRI. [23][24][25] It was shown that prebiopsy MRI scan could guide a more effective biopsy for csPCa and thus was recommended by many guidelines. 10,26 However, 16% (13/83) prostate cancers were only detected by TRUS-SBx in which 69% (9/13) were clinically significant.…”
Section: Discussionmentioning
confidence: 99%